A Spirituality for Cosmopolis - Timothy P. Muldoon (Religions)
This essay will draw from the classical Greek notions of cosmopolis and cosmopolitanism—world citizenship—as a heuristic for contemplating the question of contemporary participation in a wholly good global society. The first part of this paper will explore how the ancient notion of cosmopolis offers contemporary thinkers a compelling hermeneutic for considering cultural growth over history. Then, in part two, it will focus on spirituality, returning to the ancient Greek world through the lens of Pierre Hadot’s work on philosophy as spiritual exercise. Finally, this essay will engage Bernard Lonergan’s suggestion that cosmopolis as a heuristic is fundamentally oriented toward reversing the kinds of decline that emerge from shortsightedness and various forms of bias.